Commensurate and incommensurate oxide structures related to 2H perovskite - Battle, P; Blake, G; Burley, J; Cussen, E; Sloan, J; Vente, J; Darriet, J; Weill, F (1999)
The magnetic structures of Ca3LiRuO6 and Ca3NaRuO6 have been deduced from powder neutron diffraction data. In each case successive Ru5+ cations in the [001] chains of the Sr4PtO6-like structure are antiferromagnetically coupled, and nearest-neighbour Ru5+ cations in adjacent chains are also antiferromagnetically coupled. ©1999 Materials Research Society.